Sales and Marketing for Travel and Tourism / Second Edition - Davidoff Doris S; Davidoff Philip G (Prentice Hall Career & Technology, 1994)
Preface, Acknowledgements, Introduction, The Nature of the Tourism Product, Psychology of the Traveller, Market Research, Image, The Marketing Mix in Travel and Tourism, Pricing, Communication, Relationship Marketing, Advertising and Publicity and Promotion, Using Print and Broadcast Media Effectively, The Sales Function in the Travel Industry, Sales Techniques, The Sales Interview, Service - The Most Important Marketing Tool, Technology and Marketing, Marketing in Travel and Tourism - Present and Future, Index.